Modified simplification of HDM-4 methodology for the calculation of vehicle operating cost to incorporate terrain and expanded to all vehicle types for use in the Western Cape context - Hofmeyr, Melanie Kemp (Stellenbosch : Stellenbosch University, 2015)

(untitled)
Thesis (MSc)--Stellenbosch University, 2015.